Effectiveness of the Job Loss Guarantee Program (JKP) in Responding to the Phenomenon of Mass Layoffs in Indonesia in 2025 - Tarigan, Rapha Efrani; Sinaga, Hanna; Sitorus, Krista Putri; Grace G. Priscilia Sitinjak; Habieb Pahlevi; Riady, Yasir; Lina Gurung (International Journal of Sustainable Business, Management and Accounting, 2025)
Background of study: The phenomenon of mass layoffs in 2025 presents a serious challenge to Indonesia’s labor force, affecting household economic stability and increasing social risks. As a response, the government implemented the Job Loss Guarantee Program (JKP) as part of a broader social protection strategy to safeguard workers' welfare. Aims and scope of paper: This study aims to evaluate the effectiveness of the JKP program in mitigating the impact of mass layoffs, with a focus on benefit distribution, access to employment information, job training quality, and public satisfaction. Methods: The study applied a qualitative approach through literature and documentation analysis, using thematic content analysis of secondary data obtained from government reports, national media coverage, and social media discourse. Data were analyzed descriptively to explore recurring themes in public narratives and policy implementation. Result: Findings reveal that while the JKP program has effectively provided short-term financial support and improved access to labor market information, it is hindered by complex administrative procedures, uneven benefit distribution, and job training programs that are often misaligned with current labor market needs. Informal workers remain excluded from program coverage. Conclusion: To enhance the effectiveness of the JKP program, comprehensive administrative reforms, improved competency-based training, and inclusive strategies for informal workers are necessary. This study contributes to policy evaluation discourse by highlighting implementation gaps in Indonesia’s labor protection system amid economic shocks.